PENGARUH RASIO KEUANGAN DAERAH TERHADAP PERTUMBUHAN EKONOMI KABUPATEN/KOTA DI PROVINSI ACEH - Azhari, Muhammad; Zulfa, Andria; Murtala, Murtala (J-MIND (Jurnal Manajemen Indonesia), 2020)
ABSTRACT This study aims to examine the effect of regional independence ratio, regional effectiveness ratio, regional efficiency ratio and regional income growth ratio on economic growth. The research data used is a combination of cross sections with time series in 23 districts / cities in Aceh Province during 2014-2018, which is obtained from the Budget Realization Report (LRA) issued by the Directorate General of Regional Financial Balance, Ministry of Finance (DJPK Kemenkeu). The data analysis method used is Panel Data Regression with Eviews 9 assistance.The results of this study prove that regional independence ratio, regional effectiveness ratio and regional efficiency ratio have a positive and significant effect on economic growth, while regional income growth ratio has no significant effect on economic growth in Regencies / Cities in Aceh Province Keywords:   Regional Independence Ratio, regional effectiveness ratio, regional efficiency ratio , regional income growth ratio and economics growth